PAD WELDING EFFECT ON CRANKSHAFT LENGTH WHILE MAKING BUILD-UP PROCESS - T. V. Vigerina (Наука и техника)
The paper reveals a pad welding effect on axial sizes of a crankshaft to be built-up and a dependence of axial deformation of built-up element on an elasticity modulus, a heating temperature and thermal coefficient of linear expansion of an element and a plating, weave bead sizes. This dependence enables to forecast tensile stresses in the plating. The paper contains justification on limitation of axial deformation of the built crank due to decrease of pad welding numbers up to only one during the whole period of its lifetime and carrying out  resource-saving measures.